2020
DOI: 10.1177/0022002720937750
|View full text |Cite
|
Sign up to set email alerts
|

Voting for Militants: Rebel Elections in Civil War

Abstract: Rebel actors engage in a number of behaviors beyond violent conflict, including social service provision, diplomacy, and establishing local governance. This article centers on an oft-overlooked aspect of rebel behavior and governance: rebel groups conducting popular elections in wartime. We argue that rebel elections are a means through which rebels can strengthen both local and international legitimacy, but that there are risks to employing elections (such as logistical failures or publicized disconn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 81 publications
(71 reference statements)
1
14
0
Order By: Relevance
“…Frequently, rebel elections represent an innovation over previous political institutions that exist at the local level. Consistent with our expectations, Cunningham, Huang and Sawyer (2021) similarly finds that long-term strategic objectives and ideology shape the types of institutions rebels decide to build. Relatedly, Loyle (2021) explores the conditions under which certain types of legal institutions emerge.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Frequently, rebel elections represent an innovation over previous political institutions that exist at the local level. Consistent with our expectations, Cunningham, Huang and Sawyer (2021) similarly finds that long-term strategic objectives and ideology shape the types of institutions rebels decide to build. Relatedly, Loyle (2021) explores the conditions under which certain types of legal institutions emerge.…”
Section: Resultssupporting
confidence: 85%
“…2 By “rebel political institutions,” we refer to the range of structures and practices, both formal and informal, that rebels develop as part of a broader governance arrangement to interact with the civilian population and other unarmed actors. These institutions could resemble the forms nation-states typically adopt, such as parliaments and political parties (Cunningham, Huang and Sawyer 2021), they could appropriate traditional sources of authority (such as chiefs or civilian councils), or they could depart from institutional forms commonly found in sovereign nation-states.…”
Section: Conceptualizing and Comparing Rebel Political Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Colombia, civilian resistance to rebel governance was less likely in areas where pre-existing institutions were both legitimate and effective (Arjona 2016, 71). Additionally, new research in this special issue has found that rebel governance is shaped by the legacy of pre-existing political institutions (Mampilly and Stewart 2021), that some rebel groups have created parallel judicial systems in contexts where state legal systems are viewed as corrupt (Loyle 2021), and that some rebel groups conduct elections as a strategy to differentiate themselves from incumbent states (Cunningham, Huang, and Sawwyer 2021). I build upon these findings to argue that civilian perceptions of the quality of governance provided by an incumbent state affects the displacement decisions of civilians living in territory captured by a rebel group that offers them a competing political order.…”
Section: A Theory Of Competitive Governance and Displacement Decisionsmentioning
confidence: 99%
“…In “Voting for Militants,” Cunningham, Huang, and Sawyer argue that rebel elections play a key role in eliciting external support by “cultivating legitimacy among international audiences” (Cunningham, Huang, and Sawyer 2021, 89). In addition to any localized benefits, observable (and often publicized) elections provide information to the international community and signal an openness to democratic practice and accountability toward civilians regardless of the rebels’ actual commitment to such principles.…”
Section: Dynamic Processes Of Rebel Governancementioning
confidence: 99%